2005
DOI: 10.1128/aem.71.7.3761-3769.2005
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Trehalose Production Improves Growth of Escherichia coli under Osmotic Stress

Abstract: The biosynthesis of trehalose has been previously shown to serve as an important osmoprotectant and stress protectant in Escherichia coli. Our results indicate that overproduction of trehalose (integrated lacI-P tac -otsBA) above the level produced by the native regulatory system can be used to increase the growth of E. coli in M9-2% glucose medium at 37°C to 41°C and to increase growth at 37°C in the presence of a variety of osmotic-stress agents (hexose sugars, inorganic salts, and pyruvate). Smaller improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
129
0
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(138 citation statements)
references
References 46 publications
4
129
0
2
Order By: Relevance
“…Zhou et al (2006) reported that d-())-lactate synthesis significantly increased when betaine was added to the culture medium as an osmoprotectant. It was likewise found that modification of the trehalose content in recombinant E. coli also resulted in higher growth (Purvis et al 2005), and trehalose-dependent stress tolerance was identified as a relevant trait for industrial purposes involving baker's yeast (Attfield 1997). A compatible solute like glycerol could serve not only as the main carbon source, but also as a relevant osmoprotectant, thus enhancing the behaviour of the ethanologenic strains.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al (2006) reported that d-())-lactate synthesis significantly increased when betaine was added to the culture medium as an osmoprotectant. It was likewise found that modification of the trehalose content in recombinant E. coli also resulted in higher growth (Purvis et al 2005), and trehalose-dependent stress tolerance was identified as a relevant trait for industrial purposes involving baker's yeast (Attfield 1997). A compatible solute like glycerol could serve not only as the main carbon source, but also as a relevant osmoprotectant, thus enhancing the behaviour of the ethanologenic strains.…”
Section: Discussionmentioning
confidence: 99%
“…Since there are several reactions where UDP-glucose is used in biosynthesis [e.g. trehalose production in E. coli (Purvis et al, 2005)], perhaps some of these reactions are reversible enough in Aeromonas galU mutants to generate the low amount of UDP-glucose needed to introduce a single glucose residue into the LPS-core.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, carbohydrates may act as signaling molecules (Hanson and Smeekens 2009) and play a role in adaptive mechanisms to stress (Ramel et al 2009). Moreover, trehalose, a rare, non-reducing disaccharide, the presence of which was multiple times related to stress tolerance in bacteria (Purvis et al 2005) and fungi (Cao et al 2008), also accumulates in plants and seems to play a protective role during abiotic stress; however, its specific function is not well understood. In general, trehalose is not accumulated at high levels and, except some resurrection plants, it is barely detectable in crop plants (Fernandez et al 2010).…”
Section: Carbohydratesmentioning
confidence: 99%